The Biological Half-Time of Hageman Factor - Veltkamp, J. J; Loeliger, E. A; Hemker, H. C (Thrombosis and Haemostasis, 1965)
The biological half-time of factor XII was assessed (a) after transfusion of freshly-drawn, normal intact ACD-plasma into a patient having Hageman trait and suffering from polycythaemia vera, and (b) with blocked synthesis in a patient suffering from acute liver dystrophy due to phosphoric intoxication. The results obtained suggest that the biological half-time under normal conditions has a value between 50 and 70 hrs.